Documentos de Benedicto XIII referentes a la Corona de Castilla - ALVAREZ PALENZUELA, VICENTE ANGEL (Historia del Derecho, 2021)
This work brings together all the documentation of Benedict XIII, held in the Registros Avignonenses and Registros Vaticanos of the Vatican Apostolic Archives, relating to the Crown of Castile. It includes 8144 documents arranged chronologically from the beginning of the pontificate until the withdrawal of obedience by the Kingdom of Castile logically extinguished the issuing of documents for this purpose. The content of the documentation covers all the broad aspects of the Pontifical Chancery: provision of dioceses and abbeys, granting of benefices, spiritual graces and indulgences; appointment of collectors, legates and judges in the most diverse lawsuits. All the politics of the Castilian kingdom and its international implications are reflected in this documentation. And, in particular, in relation to the serious situation of division that the Church of the time was going through. The Documentary Collection is preceded by a Preliminary Study in which some aspects of the Pontificate of Benedict XIII are analysed, some other aspects of special interest contained in the documentary collection are highlighted, and some lines of research are pointed out, together with a bibliographical contribution that allows us to expand on each of the issues analysed. Particularly useful for local history aspects of each of the dioceses and also for prosopographical studies.